Transparency of electoral accountability in amazonian municipalities - Gabriele Assunção da Silva; Aline Gomes Peixoto (Revista Ambiente Contábil)
Purpose: The general objective of the article is to analyze whether the electoral accountability of mayoral candidates during the 2020 Amazonian municipal elections promotes transparency in campaign financing and to compare financing with re-election in the electoral contest.